The targum of Zephaniah : manuscripts and commentary - Ho, Ahuva, 1943- (Studies in the Aramaic Interpretation of Scripture, 2009)
This seminal and comprehensive study of Targum Jonathan to Zephaniah focuses on two major facets of exegesis: The twenty-one manuscripts from five different provenances, reflecting a variety of textual traditions and scribal erudition, thus revealing distinct stemmas; and the history of transmission of Targum Jonathan. Divergences from the literality of the MT unveil the emotions - fear, dismay, and hope - and the prayers of the meturgeman, as he reacts to historical events in the near past and in his own time.